Sexual hybridization among azolla species - Cat, Do Van; Watanabe, Iwao; Zimmerman, W.J.; Lumpkin, T.A.; Baillonville, T. de Waha (Canadian Science Publishing, 1989)
Sexual hybridization, one of possible methods to improve agronomic traits of Azolla, was tried among Azolla filiculoides Lamarck, Azolla microphylla Kaulfuss, Azolla mexicana Presl., and Azolla pinnata R.Br. Crosses between A. filiculoides and A. microphylla were successful. Hybrids from A. microphylla (female) and A. filiculoides (male) were studied in detail. Electrophoresis of enzymes, shikimate dehydrogenase, phosphoglucomutase, and 6-phosphogluconate dehydrogenase, showed that enzyme loci of hybrids shared those of one or both parents. Hybrids produced only microsporocarps. Stem length of the hybrid was intermediate between those of both parents. Azolla filiculoides has longer stems than A. microphylla. Red color appeared in hybrids but not in both parents in the field and in the greenhouse under the P- or Ca-deficient condition. Fresh biomass production of hybrids at 37 °C: 29 °C 12-h light: 12-H dark was lower than that of A. microphylla and higher than that of A. filiculoides. The N content of hybrids was higher than that of A. microphylla. Growth of hybrids in the field was greater than that of A. microphylla strains, indicating positive heterosis. Key words: Azolla, Azolla filiculoides, Azolla microphylla, sexual hybridization, heterosis.